THE FINAL YEAR OF MEDICAL SCHOOL TOGETHER WITH THE COVID-19 PANDEMIC WAS RELATED TO EMOTIONAL EATING BEHAVIOR - Muhammad Ihsan Abdurrahman; Syarif Husin; Evi Lusiana; Ardesy Melizah Kurniati; Tri Suciati (Majalah Kedokteran Sriwijaya, 2022)
Emotional eating, or overeating to ease unpleasant emotions, is one of the harmful impacts of stress. Students in their final year of college are more susceptible to emotional eating because their stress level is high. The main purpose of this study was to examine the association between stress and emotional eating behavior in final-year Medical Education Study Program students of Universitas Sriwijaya. Data was collected in January 2021, with as many as 121 students from the 2017 class participating. The Perceived Stress Scale (PSS) questionnaire was used in this study to assess students' stress levels, while the Dutch Eating Behaviour Questionnaire (DEBQ) was used to assess emotional eating behavior. The Chi-square test was used to examine the data. Overall, this study discovered that 19 students (15.7 percent) were classified as having low stress, 82 students (67.8 percent) as having moderate stress, and 20 students (16.5 percent) as having high stress. Emotional eating affects up to 74 (61.2%) of students, with female students experiencing more. The Chi-square test yielded p=0.018 (p 0.05) and OR 3.282 (1.186-9.081) indicating a significant link between stress and emotional eating behavior in final-year Medical Education Study Program students of Universitas Sriwijaya.